An Asynchronous Concerted Mechanism and Its Origin in Lewis Acid‐Mediated Carbonyl‐Olefin [2+2] Cycloaddition - Li, Yan‐Yu; Zhang, Shuo‐Qing; Hong, Xin (Chemistry, an Asian journal, 2023)
The concerted mechanism of thermal BBr3‐mediated [2+2] carbonyl‐olefin cycloaddition is intriguing considering the conflict against the Woodward–Hoffmann rule. In this work, we report a mechanistic study of the titled reaction using density functional theory calculations. The concerted [2+2] cycloaddition mechanism is operative even for the truncated model system of 2‐methyl‐2‐butene and butanone. Intrinsic reaction coordinate analysis and potential surface mapping showed the asynchronous nature of the apparent concerted [2+2] cycloaddition, resulting from the proximity of carbocation‐oxyanion in the transient zwitterionic structure. Solvent effects can change the reaction to a stepwise mechanism, highlighting the importance of zwitterion stability. Building upon this finding of the asynchronous concerted or stepwise [2+2] cycloaddition mechanism, two mechanistic classifications were elaborated based on substrates containing varied substituents and Lewis acids, with a focus on manipulating the stability of positive carbocation and negative oxyanion in the transient zwitterionic species. Thermal BBr3‐mediated [2+2] cycloaddition violates the Woodward–Hoffmann rule. This study investigates the underlying mechanism of this reaction through DFT calculations, revealing an asynchronous concerted [2+2] cycloaddition mechanism via oxetane and its origin from IBO analysis. These findings confirmed the crucial rule of the stability of zwitterionic structure and provide a mechanistic guide for Lewis acid‐mediated carbonyl‐olefin [2+2] cycloaddition.